Connecting detectives : the influence of 19th century sleuth fiction on the early hard-boileds - Moore, Lewis D. (McFarland & Company, Inc., Publishers, 2015)
"A literary examination of the influence of 19th-century sleuths on the early hard-boiled investigators, this book explores the importance of works by Poe, Dickens, Collins and Conan Doyle to the development of detective series. Authors from the transitional and modern periods are also discussed to show the ongoing influence of the 19th century detective writers"--